Autopilot simulator prototype for autonomous driving based on SimTwo - Abreu, Adérito Daniel Mendes (2020)
The main objective of this work was to develop a control system for an autonomous vehicle that provides autonomous driving. For this, a simulation software, named "SimTwo" was used, where the actuation and sensing model was developed. At the end of the work, a control and 3D visualization system was obtained for an autonomous vehicle capable of driving on a road, avoiding obstacles, alerting in case of danger, among others. The work was developed in a simulation environment and includes a 3D model of a road, with several real scenarios, where the vehicle moves. There are objects on the circuit that can obstruct the passage of the car, creating situations of imminent danger. This system alerts the driver in the event of danger and reacts by deflecting or stopping. This control system uses image sensors and LiDAR (Light Detection And Ranging) as inputs data sources.